KELAYAKAN INSTRUMEN PENILAIAN BERBASIS ISPRING SUITE PADA MATERI POLA BILANGAN - Shinta Anjelina; Nur Ainnul Mardiah; Qadriah Triatni Putri; Karmila Sari; Farman Farman (Universitas Muhammadiyah Semarang, 2021)
The purpose of this study was to test the feasibility of the ispring suite-based assessment instrument on the number pattern material. This research method uses 3 stages of the 4D model, namely define, design, development. The research subjects were students of class VIII at MTs. S Nurul Iman Pomalaa. The data analysis technique used expert validation questionnaires and student response questionnaires. The results obtained: material expert validation got a final score of 4.31 with valid criteria, media experts got a final score of 4.5 with valid criteria. The results of the student response questionnaire obtained a final score of 4.3 including a positive response. So it can be concluded that the assessment instrument for learning mathematics with the Ispring Suite-based number pattern material has been tested for its feasibility to be used as an assessment instrument.